Cardiac Amyloidosis: Internist and Cardiologist Insight - E. V. Reznik; T. L. Nguyen; E. A. Stepanova; D. V. Ustyuzhanin; I. G. Nikitin (SINAPS LLC, 2020)
Cardiac amyloidosis (amyloid cardiomyopathy) is a disease damage to the heart caused by extracellular amyloid deposition. In some cases, there may be local damage to the structures of the heart, for example, the atria; more often, heart damage is part of a systemic (generalized) pathology. Depending on the amyloid precursor protein, 36 types of amyloidosis are described, among which hereditary and acquired forms are distinguished. Cardiac amyloidosis is diagnosed 1) in the case of the amyloid infiltration in the myocardial bioptates or 2) in the case of non-cardiac amyloid deposition and the left ventricular wall thickening >12 mm without arterial hypertension and other reasons. The heart is most often affected in AL-, ATTR-, AA-, AANF-types of amyloidosis. Cardiac amyloidosis should be considered in patients with a heart failure with an unclear etiology, especially with preserved left ventricular ejection fraction, refractory to treatment, with proteinuria and CKD 4-5, in patients with idiopathic atrial fibrillation and conduction disturbances, in patients with left ventricular wall thickening of unclear etiology, low ECG voltage, unexplained arterial hypotension and pulmonary hypertension. Screening for cardiac amyloidosis should include non-invasive methods such as electrophoresis and immunofixation of blood and urine proteins, the free light lambda and kappa chains of immunoglobulins, 99Tc-DPD scintigraphy, genetic testing (if hereditary variants of amyloidosis are suspected), as well as a histological examination of biopsy samples stained with Congo red and polarizing microscopy.